Non-linear conduction due to depinning of charge order domains in Fe3O2BO3 - Dos Santos, E. C. [UNESP]; Da Silva, E. F. [UNESP]; Fernandes, J. C.; Ghivelder, L.; Freitas, D. C.; Continentino, M. A.; Walmsley, L. [UNESP] (IOP Publishing, 2017)
The oxyborate Fe3O2BO3 presents a charge density wave (CDW) transition close to room temperature. As we show here, this is associated with a well defined anomaly in the specific heat. Below this transition, when applying in a single crystal of Fe3O2BO3 a DC voltage above a temperature dependent threshold, a high current is liberated in this material. We study the conduction in single crystals of Fe3O2BO3 with voltage applied parallel and perpendicular to the crystallographic c axis direction. The observed currents are attributed to the depinning of charge ordered domains above a threshold voltage V T2 that gives rise to a collective conduction due to coherent domains. Compliance limited DC data shows that above a lower threshold voltage depinning is smooth and follows a power law scaling. Similar depinning with power law scaling is also revealed in the AC conductivity.
Keywords: charge density wave; charge ordering; non-linear conductance; oxyborates; structural phase transition; transition metal oxides